Exploratory study on the development of native soil cyanobacteria in the province of Córdoba - Murialdo, R. (2016)
Fil: Murialdo, R. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.